2019
DOI: 10.1186/s12284-019-0291-0
|View full text |Cite
|
Sign up to set email alerts
|

Aeration Increases Cadmium (Cd) Retention by Enhancing Iron Plaque Formation and Regulating Pectin Synthesis in the Roots of Rice (Oryza sativa) Seedlings

Abstract: Background Aeration and water management increasing rhizosphere oxygen amount significantly promote rice ( Oryza sativa ) growth and yield, but the effect of root aeration on cadmium (Cd) toxicity and accumulation in rice seedlings under hydroponic culture remains unclear. Results Results showed that aeration promoted rice seedling growth and alleviated Cd toxicity. Transverse section discovered that Cd accelerated root mature and senescence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 78 publications
1
16
0
Order By: Relevance
“…1, with Cd treatment, the Cd concentrations in the root would be higher than 2000 mg kg −1 dw, and those in the shoot were approaching to 500 mg kg −1 dw. The ranges of Cd concentrations in rice seedlings were also found in the recent studies by using (Chiao et al 2019;Li et al 2019). The TF values, that almost all were less than 0.2, indicated that most of the Cd uptake by rice plants was accumulated in the root rather than being transferred to the shoot.…”
Section: The Cultivar Variations In CD Toxicity and Distribution In Rsupporting
confidence: 69%
See 2 more Smart Citations
“…1, with Cd treatment, the Cd concentrations in the root would be higher than 2000 mg kg −1 dw, and those in the shoot were approaching to 500 mg kg −1 dw. The ranges of Cd concentrations in rice seedlings were also found in the recent studies by using (Chiao et al 2019;Li et al 2019). The TF values, that almost all were less than 0.2, indicated that most of the Cd uptake by rice plants was accumulated in the root rather than being transferred to the shoot.…”
Section: The Cultivar Variations In CD Toxicity and Distribution In Rsupporting
confidence: 69%
“…In the early study, Zhang and Duan (2008) have ever used the treatment of 50 µM Cd in hydroponics to investigate the genotypic difference in Cd accumulation. Recently, the same treatment level of 50 µM Cd was also used by Li et al (2019) for investigation of Cd retention in the roots of rice seedlings. The treatment level of 50 µM Cd in hydroponics could result a significant reduction in root and shoot growths and increases of plant Cd concentrations for the different rice cultivars (Shi et al 2005;Zhang and Duan 2008).…”
Section: Plant Materials and CD Treatment In Hydroponicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to O 2 flux measurement, the microsensor should be calibrated with measuring solution (0.1 mM KCl, 0.1 mM CaCl 2 , 0.1 mM MgCl 2 , 0.5 mM NaCl, 0.3 mM MES, 0.2 mM Na 2 SO 4 , pH 6) containing different concentrations of O 2 (N-saturated and control cultural media). Only when the Std Curve is between −2000~−9000 pA/mM can the microsensor be placed in the blank measuring solution for polarization for 1 h, until the net O 2 flux is near baseline, at which time the microsensor can be used [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the early study, Zhang and Duan (2008) have ever used the treatment of 50 µM Cd in hydroponics to investigate the genotypic difference in Cd accumulation. Recently, the same treatment level of 50 µM Cd was also used by Li et al (2019) for investigation of Cd retention in the roots of rice seedlings. The treatment level of 50 µM Cd in hydroponics could result a signi cant reduction in root and shoot growths and increases of plant Cd concentrations for the different rice cultivars (Shi et al, 2005;Zhang and Duan, 2008).…”
Section: Plant Materials and CD Treatment In Hydroponicsmentioning
confidence: 99%